Child feeding practices among working mothers and daycare staff in Jakarta, Indonesia: A mixed-methods study - Setiyaningrum, Hanna Yuni; Anggorowati, Rita; Fahmida, Umi (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada, 2025)
Background: Child-feeding practices among working mothers and daycare staff play an essential role in children’s dietary intake.Objective: This study aims to compare child-feeding practices between working mothers and daycare staff. Additionally, the study explores the perspectives of working mothers, daycare staff, and management regarding their roles in child feeding practices to the children.Methods: Mothers of under-five children (n=124) who used daycare facilities in 11 daycares in Ministry/Agencies in Jakarta and the daycare staff (n=47) were invited to complete the self-administered Child Feeding Practices Questionnaire (CFPQ). Qualitative research utilized WeValue Insitu and Perspective Exploration (PEX) involving working mothers (n=3), daycare staff (n=5), and daycare management staff (n=5).Results: The findings indicated higher scores amongst working mothers on child control (3.20 vs 2.20, p<0.001) and emotion regulation (2.00 vs 1.67, p<0.001) subscales than daycare staff. On the other hand, daycare staff had higher scores on pressure to eat (3.75 vs 3.50, p<0.05), encourage balance and variety (4.75 vs 4.50, p<001), modelling (5.00 vs 4.25, p<0.001), and restriction (4.20 vs 3.40, p<0.001) subscales than the working mothers. The quantitative findings were supported by the qualitative findings regarding the child feeding practices, especially for restriction, encourage balance and variety, and modelling subscales.Conclusions: The study highlights complementary roles of mothers and staff in shaping children’s eating behaviours and the importance of communication between mothers and daycare staff on the child's feeding practices. Nutrition education is needed, particularly to strengthen aspects of child feeding which are still low in mothers and daycare staff.